Coesite Formation at Ambient Pressure and Low Temperatures - J. R. Martínez; A. Vázquez-Durán; G. Martínez-Castañón; G. Ortega-Zarzosa; S. A. Palomares-Sánchez; Facundo Ruiz (Advances in Materials Science and Engineering)
Partial crystallization of silica xerogel in the form of coesite has been obtained at low-pressure conditions and temperatures of ∼565∘C, in samples containing chlorophyll aggregates dispersed in amorphous silica. Silica xerogel samples were prepared by the sol-gel method using an ethanol:H2O:TEOS molar ratio of 4:11.6:1 and loaded with extracts from frozen spinach leaves. The silica xerogel microstructure of the powders was studied as a function of annealing temperature. It was found that partial crystallization of the glass matrix in the form of coestite was obtained at lower pressure than those specified by the phase diagram. Chlorophyll aggregates were added to the starting solutions which, upon thermal treatments, form small colloidal particles in the glass matrix. The presence of coesite is corroborated by the Rietveld refinement method.